Estratégias de controle para grupo motor-gerador a etanol operando com velocidade variável - Magnago, Henrique de Souza (2019)
This master thesis presents two strategies for speed control and power generation by a variable speed ethanol generator set (genset), where the power generated is reflected in the current of the battery bank. Initially, the internal combustion engine model (MCI) is presented, which converts the chemical energy present in the fuel into mechanical energy, and then converted into electric energy by a permanent magnet synchronous generator (PMSG). This model presents simplifications so that it can be identified using only variables already available in a genset, such as throttle opening, manifold pressure, speed and load torque. In addition, a methodology for obtaining the model parameters is proposed. The two control strategies consist of: Controlling the speed via the MCI and the battery current via the PMSG; or control the speed via the PMSG and the battery current via the MCI. In both cases, it is necessary to control precisely the opening of the throttle valve, thus, the control of the throttle valve position is also presented. Both genset control strategies are compared using experimental data, where it is possible to evaluate the performance of the speed control and the battery current control. In addition, a new control strategy for the output inverter is proposed, consisting of an internal current loop and an external voltage loop, where a load current predictive observer is used.